Pengaruh Pendidikan Kesehatan dengan Media Booklet Terhadap Pengetahuan, Sikap dan Tindakan Ibu Tentang Stimulasi Perkembangan Anak Usia Pra Sekolah di Wilayah Kerja Puskesmas Lubuk Buaya Kota Padang - Melda Saputri; Eva Chundrayetti; Deswita Deswita (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Children are the next generation of the nation, so it takes children with good quality in order to achieve a quality future of the nation. The reality is that low and middle income countries cannot realize the full development potential of children. Appropriate stimulation is needed such as with booklet media so that children develop well. This research is a quantitative study using the "Pre and Post test Control Group" design which aims to see the effect of health education with booklet media on knowledge, attitudes and actions about stimulating the development of preschool children in the work area of the Lubuk Buaya Health Center, Padang City. The population is 959. The sample is 34 respondents, 17 respondents in the intervention group and 17 in the control group. There was an effect of health education on knowledge (p=0.002), attitude (p=0.004) and action (p=0.006) in the intervention group. There was no effect of health education on knowledge (p=0.163), attitudes (p=0.083) and actions (p=0.183) in the control group. It is hoped that nurses in the community educate mothers about stimulating child development and it is hoped that mothers will take the time to read booklets, carry out all forms of stimulation to children according to what is listed in the booklet.